Study of Indonesia's Economic Development Based on Sharia Economic Law Philosophy and MUI Fatwa - Juarsa, Eka; Syarif, Nurrohman; Kania, Dede; Imaniyati, Neni Sri (Syiar Hukum, 2025)
This library research focuses on books and literature as primary sources. It provides an overview of Indonesia's economic development from the perspective of sharia economic law philosophy and its application in DSN-MUI fatwas. Islamic economic philosophy is rooted in the Qur'an and Sunnah, which also guide DSN-MUI in formulating fatwas addressing economic issues. DSN-MUI plays a strategic role in developing sharia economic law to meet society's need for legal fatwas on economic activities, particularly in response to evolving product innovations.